Regulating for the equitable remuneration of music artists in Kenya - Nyehita, Suzanne (Department of Commercial Law, 2025)
Music artists are usually incentivized to create when they receive royalties or revenue from the commercialization of their music. Although copyright and related rights initially vest with music artists to enable them to extract the full value of their exclusive rights, many lack the resources to achieve commercial success independently. They often assign or license rights to intermediaries, leading to less favourable remuneration compared to the substantial earnings of powerful intermediaries. These contractual relationships are often shaped by unequal bargaining power, favouring intermediaries who control transactions and set remuneration terms. Some scholars argue that disparities are inherent in the music business model and unrelated to fairness/equity. Others contend that the position of music artists has improved, particularly for high profile artists with corporate-affiliations and access to professional services. However, many music artists still lack the market power of larger intermediaries and struggle to secure favourable remuneration. This thesis explores the unequal dynamics between music artists and intermediaries, advocating for state intervention to promote equitable revenue distribution. It proposes a benchmark test grounded in the Rawlsian theory of justice and legislative interventions that prioritize protecting music artists as the least advantaged stakeholders. The thesis advances Rawls' application to copyright by focusing on the exercise of music artists' exclusive rights in contractual relationships with intermediaries. It outlines four principles: justice in the initial and subsequent acquisition of rights, transitional justice for reforms and reparative justice. Highlighting shortcomings in Kenya's copyright system, it recommends reforms informed by insights from Germany and South Africa.